The Effects and the Mechanisms of Board Gender Diversity: Evidence from Financial Manipulation - Wahid, Aida Sijamic (Journal of business ethics, 2019)
This study examines the impact of board gender diversity on financial misconduct. The findings suggest firms with gender-diverse boards commit fewer financial reporting mistakes and engage in less fraud. The findings hold after accounting for the potentially endogenous nature of board demographic characteristics via instrumental variable approach. Furthermore, the findings are consistent in pre- and post-regulation (Sarbanes–Oxley) periods and hold for firms with good and bad governance. The findings do not seem driven by differences in effort or quality, in terms of independence and expertise, of female and male directors. The benefit derived from increasing the number of female directors on corporate boards seems to diminish at higher levels of gender diversity, indicating that impact of gender diversity on decreasing the likelihood of financial misconduct may be a result of a change to board group dynamics.